KONSULTASI DAN PEMBINAAN AWIG-AWIG DI DESA PAKRAMAN JUNJUNGAN KECAMATAN UBUD-GIANYAR - A.A. G. Oka Parwata; K. Wirta Griadhi; I N. Wita; I.G.A. Mas Rwa Jayantiari (Buletin Udayana Mengabdi, 2013)
As it is widely recognized that community empowerment in tertiary education provides a wide chance to keepin touch with the community members. This is in order to get new experience and to dedicate the knowledgefor others. This community empowerment activity aims at guiding community members of Junjungan village inGianyar Regency, Bali to reformat and to revise the substance of their traditional law. Traditional law which isknown as awig-awig in Junjungan customary village has been documented in written form. It also has been usedas the code of conduct for the community members of Junjungan customary village for 10 years. However, theawig-awig has yet not considered representative that it has not been responsive to represent the people’s need anddevelopment in the community. Besides, this village is located in a strategic area of Ubud which is known as oneof the tourist centers in Bali. As a result, the revision of awig-awig that makes it more responsive to communitydevelopment is significantly needed. The method utilized in this event is discussion and consultation in whichthe community members are actively involved in redesigning their awig-awig. The techniques on how to writethe articles in the traditional law are also the main focus in this event. All community leaders and communitymembers involved in this event and gave their support so that a new guidance in the revision of the awig-awigof Junjungan village is successfully made and redesigned. In addition, the event can be carried out on time basedon its plan and timeline.